A Review of Research on the Neurocognition for Timbre Perception - Wei, Yuyan; Gan, Lin; Huang, Xiangdong (Frontiers in Psychology, 2022)
As one of the basic elements in acoustic events, timbre influences the brain collectively with other factors such as pitch and loudness. Research on timbre perception involve interdisciplinary fields, including physical acoustics, auditory psychology, neurocognitive science and music theory, etc. From the perspectives of psychology and physiology, this paper summarizes the features and functions of timbre perception as well as their correlation, among which the multi-dimensional scaling modeling methods to define timbre are the focus; the neurocognition and perception of timbre (including sensitivity, adaptability, memory capability, etc.) are outlined; related experiment findings (by using EEG/ERP, fMRI, etc.) on the deeper level of timbre perception in terms of neural cognition are summarized. In the meantime, potential problems in the process of experiments on timbre perception and future possibilities are also discussed. Thought sorting out the existing research contents, methods and findings of timbre perception, this paper aims to provide heuristic guidance for researchers in related fields of timber perception psychology, physiology and neural mechanism. It is believed that the study of timbre perception will be essential in various fields in the future, including neuroaesthetics, psychological intervention, artistic creation, rehabilitation, etc.